2000
DOI: 10.1086/312658
|View full text |Cite
|
Sign up to set email alerts
|

New Evidence for the Complex Structure of the Red Giant Branch in ω Centauri

Abstract: We report on the complex structure of the red giant branch (RGB) of omega Centauri, based on a new wide-field and wide-color baseline B and I photometry. Our color-magnitude diagram (CMD) shows the presence of multiple populations along this branch; in particular, we discovered an anomalous branch (RGB-a), which appears to be well separated from the bulk of the RGB stars. On the basis of our CMD and from the previous literature, we conclude that (1) these stars, clearly identified as a separate population in o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
350
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 225 publications
(373 citation statements)
references
References 18 publications
22
350
1
Order By: Relevance
“…(1999) observed a clear evidence of multiple stellar populations in w Centauri. These results were confirmed by Pancino et al (2000) in a photometric study involving 230,000 stars in this cluster.…”
Section: Are Some Globulars the Remnant Cores Of Dwarf Ellipticals?supporting
confidence: 74%
“…(1999) observed a clear evidence of multiple stellar populations in w Centauri. These results were confirmed by Pancino et al (2000) in a photometric study involving 230,000 stars in this cluster.…”
Section: Are Some Globulars the Remnant Cores Of Dwarf Ellipticals?supporting
confidence: 74%
“…Following the suggestion of the referee, we propose rather that this group formed where it presently is located, and, for that same reason, is kinematically colder than the others. Pancino et al (2000) have also found that the metalpoor population is elongated along the east-west (major axis) direction, whereas the two metal-richer populations are elongated in the opposite direction. Hilker & Richtler (2000) note that the metal-richest stars are asymmetrically distributed around the center, with an excess toward the south.…”
Section: Radial Distributionmentioning
confidence: 81%
“…More-recent papers have shown that the MS is even more complex than we had previously imagined and that both the blue and the red MS host stellar subpopulations (e.g., Bellini et al 2010). The complexity of multiple stellar populations in this cluster is further demonstrated by the multiple sub-giant branches (SGBs) and red-giant branches (RGBs) and by the presence of a double white-dwarf cooling sequence (Lee et al 1999;Pancino et al 2000;Sollima et al 2005;Villanova et al 2007;Bellini et al 2010;Milone et al 2017).…”
Section: Introductionmentioning
confidence: 84%